Effectiveness of Ethanol Extract of Eugenia polyantha Wigh in Inhibiting Streptococcus mutans - Syaflida, Rahmi; Riza, Ahyar; Siregar, Indra Basar; Ravichandran, Pavitra (Dentistry Faculty, 2023)
Background: Many microorganisms can be found within the oral cavity, including Streptococcus mutans. The introduction of oral bacteria into the bloodstream can lead to the occurrence of bacteremia and subsequent development of systemic diseases. Traditional medicine uses specific ingredients or herbs employed over successive generations and is widely believed to possess medicinal properties. One example is the bay leaf, scientifically known as Eugenia polyantha Wight. Objective. This study aims to determine the effectiveness of bay leaf extract (Eugenia polyantha Wight.) in inhibiting Streptococcus mutans. Materials and Methods: This type of research is an experimental laboratory with Post-test Only Control Group Design. Testing the effectiveness of antibacterial in this study using the diffusion method by diluting bay leaf extract using DMSO solvent into five concentrations, namely 50%, 25%, 12.5%, 6.25%, and 3.125%, with a sample size of 4 for each concentration. Results: The results showed that bay leaf extract concentrations of 50%, 25%, 12.5%, 6.25%, and 3.125% showed a clear zone around the disc paper in Muller Hinton Agar as a medium for the breeding of Streptococcus mutans bacteria. The formation of a clear zone indicates that the ability of bay leaf extract inhibits the growth of Streptococcus mutans with a mean diameter of inhibition of 10.4 0.2944 mm; 8.9 0.7500 mm; 7.1 0.3202 mm; 6.9 0.2944 mm; and 6.4 0.1826 mm. Conclusion: Eugenia polyantha Wight can inhibit the development of Streptococcus mutans. A concentration of 50% is the best in inhibiting the development of Streptococcus mutans based on the growth zone of bacteria.